A novel method for autophagy detection in primary cells: impaired levels of macroautophagy in immunosenescent T cells. - Phadwal, K; Alegre-Abarrategui, J; Watson, A; Pike, L; Anbalagan, S; Hammond, E; Wade-Martins, R; McMichael, A; Klenerman, P; Simon, A (2012)
Autophagy is a conserved constitutive cellular process, responsible for the degradation of dysfunctional proteins and organelles. Autophagy plays a role in many diseases such as neurodegeneration and cancer; however, to date, conventional autophagy detection techniques are not suitable for clinical samples. We have developed a high throughput, statistically robust technique that quantitates autophagy in primary human leukocytes using the Image stream, an imaging flow cytometer. We validate this method on cell lines and primary cells knocked down for essential autophagy genes. Also, using this method we show that T cells have higher autophagic activity than B cells. Furthermore our results indicate that healthy primary senescent CD8(+) T cells have decreased autophagic levels correlating with increased DNA damage, which may explain features of the senescent immune system and its declining function with age. This technique will allow us, for the first time, to measure autophagy levels in diseases with a known link to autophagy, while also determining the contribution of autophagy to the efficacy of drugs.